Sosialisasi Pembuatan Sabun Cuci Piring Guna MeningkatkanEkonomi Masyarakat Desa Harapan Makmur Kecamatan Sei Lepan - Melia Putri; Ardika; Winda astari (peduli riset dan pengabdian masyarakat, 2023)
Dishwashing soap is a small business, but has great potential because the need for soap in the community is quite high. The continuous consumption of dishwashing soap every day causes the need to procure soap at a high cost. The basic ingredient for making this soap is the chemical compound surfactant. which has the function of removing dirt and stains on kitchen utensils. The use of liquid dishwashing soap is easier and more effective. The purpose of carrying out entrepreneurial activities is to provide knowledge and training on making liquid dishwashing soap in order to reduce public spending on buying soap as well as to create new business opportunities